Security Enhanced Blockchain based Unmanned Aerial Vehicle Health Monitoring System - Raj, Jennifer S. (Journal of ISMAC, 2021)
In this research work and unmanned aerial vehicle (UAV) that uses blockchain methodology to collect health data from the users and saves it on a server nearby is introduced. In this paper the UAV communicates with the body sensor hives (BSH) through a low-power secure manner. This process is established using a token with which the UAV establishes relationship with the BSH. The UAV decrypts the retrieved HD with the help of of the shared key, creating a two-phase authentication mechanism. When verified, the HT is transmitted to a server nearby in a safe manner using blockchain. The proposed healthcare methodology is analysed to determine its feasibility. Simulation and implementation is executed and a performance of the work is observed. Analysis indicates that the proposed work provides good assistance in a secure environment.
Keywords: UAV; Blockchain; Healthcare; IoT; Security; Body Sensor Hives